Human immunonodeficiency virus, hepatitis B virus and hepatitis C virus: sero-prevalence, co-infection and risk factors among prison inmates in Nasarawa State, Nigeria - Moses P. Adoga; Edmund B. Banwat; Joseph C. Forbi; Lohya Nimzing; Christopher R. Pam; Silas D. Gyar; Yusuf A. Agabi; Simon M. Agwale (Journal of Infection in Developing Countries)
Background: Published data on HIV, HBV, and HCV in correctional facilities in Nigeria is scarce. We set out to establish the seroprevalence, co-infection, and risk factors for these infections for the first time among prison inmates in Nasarawa State, Nigeria. Methodology: In a cross-sectional study conducted between April and May, 2007, blood samples were collected from 300 male prisoners of a mean age of 29.2 years, in the state’s four medium-security prisons (overall population: 587). Prior to the study, ethical clearance and informed consent were obtained and structured questionnaires were administered. Samples were analyzed for HIV, HBsAg, and HCV using anti-HIV 1+2-EIA-avicenna, ShantestTM-HBsAg ELISA, and anti-HCV-EIA-avicenna, respectively. Specimens initially reactive for HIV were retested with vironostika microelisa. Data were analyzed using SPSS version 13.0. P values ≤ 0.05 were considered significant. Results: Of the 300 subjects, 54 (18.0 %), 69 (23.0 %), and 37 (12.3 %) tested positive for HIV, HBV, and HCV, respectively. Co-infections were eight (2.7 %) for HIV/HBV and two (0.7 %) for HBV/HCV. Those aged 21-26 years were more likely to be infected with HIV and HBV, while those aged 33-38 years had the highest HCV infection. Associated risk factors included duration in prison, previous incarceration (for HIV, HBV and HCV), intra-prison anal sex, multiple sex partners (for HIV and HBV), ignorance of transmission modes, blood transfusion, and alcohol consumption (for HBV and HCV). No inmate injected drugs. Conclusions: The overall outcome represents the need for prison-focused intervention initiatives in Nigeria. Injected drug use is an unlikely major transmission mode among Nigerian inmates.